Comparative Book Review on "Disability Studies Reader" by Lennard Davis & "Disability, Self, and Society" by Tanya Titchkosky - Macmbinji, Vincent (Indonesian Journal of Disability Studies, 2025)
This paper analyzes Disability, Self, and Society by Tanya Titchkosky (2003) and The Disability Studies Reader, edited by Lennard J. Davis (2006), two seminal works in the field of disability studies. Davis compiles a thorough anthology that charts the theoretical and historical landscape of the field, while Titchkosky provides a phenomenological and reflective viewpoint on disability as a lived social reality. When taken as a whole, these texts offer a multifaceted perspective on disability that emphasizes the dynamic interaction between personal experience and social norms. Together, their contributions promote a critical rethinking of how disability is viewed, discussed, and dealt with in social and academic settings.